2013
DOI: 10.1089/neu.2013.3091
|View full text |Cite
|
Sign up to set email alerts
|

Race and Insurance Disparities in Discharge to Rehabilitation for Patients with Traumatic Brain Injury

Abstract: Post-acute inpatient rehabilitation services are associated with improved functional outcomes among persons with traumatic brain injury (TBI). We sought to investigate racial and insurance-based disparities in access to rehabilitation. Data from the Nationwide Inpatient Sample from 2005-2010 were analyzed using standard descriptive methods and multivariable logistic regression to assess race-and insurance-based differences in access to inpatient rehabilitation after TBI, controlling for patient-and hospital-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 47 publications
6
97
1
Order By: Relevance
“…2,4 Patterns in availability of pediatric outpatient rehabilitation for Spanish speakers and others with LEP are particularly challenging. Other studies have documented that non-English speaking status adversely affects access to care for Latinos in the United States 20 and that, for children, parental LEP results in greater odds of children not receiving needed medical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Patterns in availability of pediatric outpatient rehabilitation for Spanish speakers and others with LEP are particularly challenging. Other studies have documented that non-English speaking status adversely affects access to care for Latinos in the United States 20 and that, for children, parental LEP results in greater odds of children not receiving needed medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies, mainly in adult populations, have described important racial and ethnic disparities in access to acute and inpatient rehabilitation services. 2,3,4,5 One pediatric study described higher unmet health care needs after TBI for non-white children and those with Medicaid insurance. 6 In addition, studies documenting outcomes after TBI have found that Hispanic and Spanish-speaking adults with TBI have poorer functional outcomes compared to non-Hispanic Whites (NHW).…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, Asemota et al reported that, among patients with traumatic brain injury, Hispanics and blacks were less likely to be discharged to supportive care compared to whites. 22 In the realm of orthopaedic trauma, a recent study by Nguyen-Oghalai et al found that racial minorities were more likely to be discharged home to self-care after hip fracture. 11 The reasons for the lower utilization of supportive services among historically disadvantaged populations remain largely unexplored and warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies reporting restricted access to supportive services for uninsured patients after traumatic brain injury and aneurysmal subarachnoid haemorrhage. 22,35 The disproportionate allocation of supportive services to insured patients might place uninsured individuals at higher risk of permanent disability. 36 On the other hand, it is possible that more care does not increase health and this issue needs to be studied for each specific condition.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Asemota et al showed that, compared with insured white patients, insured African American patients were less likely to be discharged to rehabilitation centers. 2 Furthermore, Bowman et al observed a decreased proportion of Hispanic and African American patients discharged to a rehabilitation center after TBI compared with Caucasians. 3 Additionally, studies have revealed racial/ethnic differences in follow-up after discharge.…”
Section: Discussionmentioning
confidence: 99%